Investigation on selected biotic and abiotic factors in the maintenance of the "fairy circles" (barren patches) of southern Africa - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.